Plants of medicinal use in Quissamã, Rio de Janeiro, Brazil. - Boscolo, Odara Horta (2008)
This survey was conducted between 2001 and 2002 in Quissamã, Rio de Janeiro State. Interviews with local informers were made to recollect information on the plant species used for medicinal purposes. These interviews had the objective of collecting data about the actual biological activities of the plants. Ninety-one species of plants were indicated and among them, 48 botanical families were identified. Each taxon is supplied with the scientific name, family, popular name, popular use and used part. The most representative families were Asteraceae (7), Myrtaceae (6), Lamiaceae (5), and Solanaceae (5). The leaves were the part of the plant most used (48), followed by the fruits (14). Twenty-five of the cited plants do not have any proven pharmacological activities. Tea was the most common way of their use (36%), followed by poultice (19%). The leaves were the most cited parts (49), followed by the fruits (14). The most common diseases treated with the mentioned plants were bronchitis (16) and rheumatism (15). However, the majority of plants were used according to their actual validated properties.